STUDENTS’ PERCEPTION ON THE USE OF POWTOON TOWARD ONLINE ENGLISH LEARNING - Irma Widia Mita; Eusabinus Bunau; Wardah Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
English becomes an important subject that the teacher must teach, from junior to senior high school level. Because of the online teaching and learning process, it isn't easy to teach English because the online teaching and learning process makes teachers cannot do it face to face. To make the English teaching and learning process simple and enjoyable, teachers must be familiar with the use of relevant teaching and learning material. PowToon is one of the tools that may be used as a medium for online teaching and learning. Aside from that, teachers need to know what students think about the use of animated video, particularly from PowToon. This research aims to know students' perception of the use of PowToon in online English learning. The research participants were 181 seventh-grade students of SMPN 17 Pontianak from A-F class. This descriptive research used a questionnaire and interview as the data collection. The findings of students' perception toward the use of PowToon in online learning was 75%, which is indicated as a positive perception. It means that animated videos from PowToon are recommended to become a teaching and learning media for online English Learning.